2022
DOI: 10.3389/fpls.2022.778403
|View full text |Cite
|
Sign up to set email alerts
|

Wood Nutrient-Water-Density Linkages Are Influenced by Both Species and Environment

Abstract: Tropical trees store a large amount of nutrients in their woody tissues, thus triggering the question of what the functional association of these elements with other wood traits is. Given the osmotic activity of mineral elements such as potassium, sodium, and calcium, these elements should be strong candidates in mediating the water storing capacity in tropical trees. We investigated the role of wood nutrients in facilitating wood water storage in trees by using branch samples from 48 tropical tree species in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Interestingly, T. guianensis had higher trait variation in RES (Figure 3, Table 1), a more stressful environment than DOF. Stressing environments act as filters constraining trait variation and functional diversity (Lira-Martins et al, 2022). However, the wider trait variation of T. guianensis in RES suggests that this species is well adapted to these conditions and that foliar adjustment in SD and G max are important for coping with limiting water availability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, T. guianensis had higher trait variation in RES (Figure 3, Table 1), a more stressful environment than DOF. Stressing environments act as filters constraining trait variation and functional diversity (Lira-Martins et al, 2022). However, the wider trait variation of T. guianensis in RES suggests that this species is well adapted to these conditions and that foliar adjustment in SD and G max are important for coping with limiting water availability.…”
Section: Discussionmentioning
confidence: 99%
“…T. guianensis and E. pulchrum showed an adaptive response in wood traits with variation in environmental conditions. We were not able to separate soil or climatic effects in these differences, but soil and climate represent central ecological influences on wood and leaf trait variations (Heineman et al, 2016;Cosme et al, 2017;Oliveira et al, 2019Oliveira et al, , 2021Bittencourt et al, 2022;Lira-Martins et al, 2022). The parenchyma arrangement, and more specifically the axial parenchyma, is one important characteristic that varies significantly across different taxonomic groups (Carlquist, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heineman et al (2016) showed in Panama that wood P concentration decreased with increasing wood density. Lira-Martins et al (2022) showed in the Amazon that lower wood density trees store more water in their woody tissues and have high K concentrations, certainly to regulate this reservoir. As Heineman et al (2016) also showed a good correlation between soil nutrients and wood nutrients, these results could in turn explain why lower wood density trees are limited by P and K soils, in contrast to higher wood density trees.…”
mentioning
confidence: 99%